The Effect of CAR, NPF, ROA, ROE and BI Rate on Liquidity of Sharia Commercial Banks before Become BSI - Eddy Irsan Siregar; Bagas Rahardhika; Sulhendry Sulhendry; Purwanti Purwanti (Budapest International Research and Critics University, 2022)
Islamic Banks that continue to grow are caracterized by growing asset, ehere in 2019 the number of customers reached 31,9 million, which means that only 11.94% use islamic banks as a banks to save money and other banking transactions of the total population of 267 millions inhabitans. In early 2020, the government merged all state-owned Islamic banks. This study aims to analyze the effect of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return On Asset (ROA), Return On Equity (ROE) and BI Rate on Liquidity (FDR) of Islamic Commercial Banks. These ratios are to determine whether there is an influence between the CAR, NPF, ROA, ROE and BI Rate ratios on the Liquidity (FDR) of Islamic Commercial Banks. The data used are the financial statements of Islamic Commercial Banks (BUS) for the period 2010-2019 per semester. The data used in this study are secondary data, while the population of this study includes Islamic Commercial Banks (BUS) which have financial reports (Semesteran) from 2010-2019. The sampling method used in this study was purposive sampling, in which there are 4 Islamic commercial banks that fall into the criteria of this study. The data analysis technique used in this research is panel data regression analysis using the Eviews 10 program.